SERVICE QUALITY DELIVERY AND ITS IMPACT ON CUSTOMER SATISFACTION: A STUDY OF BANKS IN BENIN CITY, EDO STATE, NIGERIA - Ugo Chuks Okolie (Universitas Pendidikan Indonesia (UPI), 2022)
In today’s ‘new normal’ in which competition is at an unpredictable speed like light, service quality and customer satisfaction are critical concepts that any service provider needs to remain competitive and sustain growth. Quality service delivery and customer satisfaction are the sword and shield of competition needed to fortify an organization to be better than the best. Therefore, this study examined the relationship between service quality and customer satisfaction in banking sector in Benin City, Edo State. The study adopted the SERVQUAL model as the main framework for analyzing service quality. Multiple regression analysis with the aid of statistical package for social science (SPSS) vision 21 was used to examine the relationships between service quality variables and customer satisfaction. The sample size of four hundred and twenty (420) was selected from the population of study through convenience sampling technique. A structured questionnaire was used to collect the needed information from the sampled respondents. Out of the 420 sample, only 292 usable questionnaires were retrieved. The results of the study showed that all service quality variables were good predictors of customer satisfaction. Customer’s positive perception is an index with exponential effects on the profitability and brand’s acceptance value proposition. To drive this strategic core value, this study provide an insight into how business and individual performance indicators can utilize the performance management tools, processes, procedure and people to close service gaps with the aim to unlock the hearts, minds and purses of customers through superior service/product that can exponentially optimize productivity and profitability. The study recommends among others that management should get rid of bureaucracy. Quality should be seen as a way of life and all blockades should be removed to ensure a holistic approach in the manner intangible service is delivered.